The construction of house price index: modelling by incorporating absolute location - Rosmera, Norshazwani Afiqah (2014)
Price of residential property plays a very important role in the economy of developed countries. Price is an element for individual or household to decide on selling and buying properties, and to invest in the direct property market. In response to such a demand, most developed countries have produced a house price index to monitor price changes. In other countries, studies related to the construction of house price index are widely conducted. However, in Malaysian context, there is less attention regarding the construction of house price index. To fill in the gap, this research aims to construct a house price index by considering absolute location in modelling the house price index. Three models of house price index (HPI) are constructed. Method used in the construction of HPI is the hedonic method. The constructed HPI models are composed of different spatial elements as explanatory variables. Spatial elements included in this research are subdistricts dummy, distance of house to city centre, and coordinate of houses. The results show that the inclusion of property coordinate helps improve the model fitting and explains variation in house price. However, in terms of price index, the inclusion of coordinate of houses may not be important as it produces a similar movement pattern with price index that is composed of common locational variable. This research reveals that the common hedonic model that is composed of subdistricts dummy and distance to city centre as locational variable is sufficient to construct an HPI.